Underdiagnosis of Dementia among Indigenous Older Adults with Cognitive Impairment. (17th December 2021) - Amano, Takashi; Gallegos, Carlos Andres; Waters, William; Freire, Wilma
Abstract: Early and timely diagnosis of dementia has been recognized as key to improving health outcomes. However, underdiagnosis among the indigenous population has not been adequately investigated. This study examines the association between indigenous ethnic identity and receiving a diagnosis of dementia and identifies factors associated with receiving a diagnosis of dementia. Data were drawn from Ecuador's Survey of Health, Welfare and Aging (SABE) – 2009, based on a probability sample of households in Ecuador with at least one person 60 years or older. This is a robust data set that allows for understanding ethnic dimensions and disparities, especially because of the successful recruitment of indigenous households. The final sample consisted of 1, 437 people who had cognitive impairment. Whether participants had ever been told that he/she had dementia was compared between the groups of people who identified themselves either as indigenous or others. Binary logistic regression analysis was utilized. Indigenous participants had a lower probability than others of receiving a diagnosis of dementia after controlling for health and function related covariates. This association became statistically insignificant after including socioeconomic factors in the model. The final model revealed that people who had higher educational attainment were more likely to receive a diagnosis of dementia. Findings suggest that underdiagnosis among indigenous older adults can be explained by their lower socioeconomic status rather than by health and functional status. This finding implies the possibility of developing strategies to promote timely diagnosis by targeting populations who are especially susceptible to underdiagnosis of dementia.